ONLINE READING PREFERENCE AND MEDIA CONTENT IN MALAYSIA: A CASE STUDY ON THE MALAYSIA SIN CHEW DAILY FACEBOOK PAGE - Leong Chew Moi; Ooi Swee Yaw (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Online reading preferences encompass the reading materials that readers favor, invest considerable effort and time into, and thoroughly enjoy. Within this context, readers have the autonomy to make their own decisions and the complete freedom to select content that most captivates their interest. Understanding the online reading preferences of audiences is crucial for media organizations and content creators. It enables them to craft content that not only attracts more readers but also retains their attention and engagement. By catering to readers’ interests, media outlets can enhance their online presence, reach a broader audience, and potentially increase revenue through increased viewership and advertisement opportunities. In Malaysia, numerous online newspaper Facebook pages cater to diverse content types such as news, entertainment, sports, feature writing, and more, aiming to cultivate readers’ interest. This study focuses on the Malaysia Sin Chew Daily Facebook Page as a case study, as it represents the most popular newspaper among readers in Malaysia. The objective is to investigate the online reading preferences of the readers. To accomplish this, a quantitative survey involving 130 respondents was conducted, utilizing content analysis to observe the "likes" and "shares" of the content. The results indicated a positive correlation between online reading preferences and media content. This research holds significant value as it can serve as a reference for organizations seeking to enhance their content to better cater to readers’ preferences.